Preparation method of sodium ion battery negative electrode material

Synthesis and carbon-coated SnS2 and Sn4P3/CoS2@rGO@C materials by hydrothermal method solve the problem of high volume expansion rate of tin-based anode material of sodium ion batteries, improve the cycle stability and conductivity of the battery, and realize the Highly efficient sodium ion battery negative electrode material.

CN119275255AInactive Publication Date: 2025-01-07ZHEJIANG WESTON NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411178373.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The volume expansion rate of the tin-based anode material of sodium ion batteries is high after complete discharge, causing the electrode material to powder and fall off, affecting the stability and capacity of the battery.

Method used

The hydrothermal method was used to synthesize SnS2@GC, SnS2@C, Sn@C and Sn4P3/CoS2@rGO@C materials. Through carbon coating and composite technology, volume expansion was suppressed, and conductivity and cyclic stability were improved.

Benefits of technology

The negative electrode material of sodium ion battery with low volume expansion rate and good conductivity is realized, which improves the cycle stability, charge and discharge efficiency and rate performance of the battery, and reduces cost and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275255A_ABST
    Figure CN119275255A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a new material, in particular to a preparation method of a sodium ion battery negative electrode material, which comprises the following steps: preparing a SnS2 material, preparing a SnS2 atGC material, preparing a SnS2 atC material, preparing Sn atC, preparing a carbon-coated Sn4P3 atC material, and preparing a Sn4P3 / CoS2 atrGO atC material. According to the invention, a hydrothermal method, a solvothermal synthesis method and a solid phase method are creatively combined to prepare the material, and the material has the advantages of high tap density, high initial charge and discharge capacity, improved mass transfer conditions, reduced concentration polarization and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a new material, and in particular to a method for preparing a negative electrode material for a sodium ion battery. Background Art

[0002] With the advancement of environmental protection, the demand for energy storage technology has further increased. The most notable feature of some clean energy sources, such as wind power and solar power generation, is that the power generation shows tidal changes. It is necessary to store electricity during the peak power generation period and release it during the peak power consumption period. Such large-scale power storage requires a large number of batteries to support it. However, with the rapid growth of demand for energy storage equipment, sodium ion batteries are particularly suitable for grid-scale energy storage systems that do not have strict requirements on equipment size due to the advantages of high natural abundance, wide distribution range, low cost, and more environmental friendliness of sodium. Energy storage applications in renewable energy have attracted more and more attention. In addition, sodium ions do not react with aluminum to form alloys, so copper foil can be used as the current collector of the negative electrode material, which further reduces the cost. At the same time, sodium ion batteries have no over-discharge characteristics and can be discharged to 0V, so they can be stored and transported in a fully discharged state, which increases the safety of storage.

[0003] Sodium-ion batteries have become a new generation of energy storage batteries with lower costs and more environmentally friendly. The volume expansion rate of the product of the tin negative electrode after complete conversion can reach 420%, which will cause the electrode material to pulverize and fall off, thus seriously affecting the stability and capacity of the battery. The solution to this problem is to reasonably design the material structure or combine a single alloying material with other materials, which can effectively inhibit the volume expansion of the electrode; the battery system we are looking for has the following characteristics: high capacity, high cycle stability, high rate performance, high initial cycle efficiency and suitable electrode voltage platform, and should also have the advantages of low cost, rich resources and little impact on the environment; tin-based material is a very promising sodium-ion battery negative electrode material, with a high specific capacity both by weight and by volume, its price is relatively low, it is not easy to burn and is non-toxic, will not harm the environment, and is relatively safe to use. Summary of the invention

[0004] In view of the above problems, the present invention provides a tin-based negative electrode material.

[0005] The first technical purpose of the present invention is to provide a SnS2@GC material with low volume expansion rate, good conductivity and high cycle stability.

[0006] The second technical purpose of the present invention is to provide a method for preparing a Sn@C material with low volume expansion rate, good conductivity and high cycle stability.

[0007] The third technical objective of the present invention is to provide a process for preparing anode material molding using the Sn4P3 / CoS2@rGO@C material.

[0008] The present invention provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps: preparation of SnS2 material, preparation of SnS2@GC material, preparation of SnS2@C material, preparation of Sn@C, preparation of carbon-coated Sn4P3@C material, and preparation of Sn4P3 / CoS2@rGO@C material.

[0009] Preferably, step (1) SnS2 material Concentrated hydrochloric acid is added to a tin tetrachloride aqueous solution, and then mixed with sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain a SnS2 material; Step (2) SnS2@GC material First, glucose is weighed and added to a polytetrafluoroethylene liner, and then the SnS2 material prepared in step (1) is added thereto, and then deionized water is added and ultrasonically stirred to uniformly disperse the SnS2 in the solution, and then the mixture is sealed and loaded into a stainless steel reactor, and then placed in a homogeneous reactor, and the reaction temperature and reaction time are set. After the reaction is completed, the mixture is naturally cooled to room temperature, and the obtained material is washed with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then placed in a blast drying oven to dry, thereby obtaining a glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material The SnS2@GC prepared in step (2) is placed in a porcelain boat, and then the porcelain boat is placed in the center of a hard glass tube and placed on a tube furnace, argon gas is introduced, and a heating program of the tube furnace is set, the temperature is increased at a rate, and then the temperature is maintained at this temperature, and naturally cooled to room temperature to obtain a black material, namely SnS2@C; Step (4) Sn@C The SnS2@C material prepared in step (3) is placed in a porcelain boat, which is placed in the center of a hard glass tube and moved to a tube furnace, into which a hydrogen-argon mixture (H2 / Ar) is introduced, and the temperature is increased at a program rate, and then the temperature is maintained at this temperature, and naturally cooled to room temperature to obtain a Sn@C material; Step (5) Carbon coating of Sn4P3@C material The Sn@C material prepared in step (4) and red phosphorus are mixed and ground in a mortar to make the two materials fully mixed, and then added to a polytetrafluoroethylene liner, and ethylenediamine is slowly added thereto and stirred, and the liner is placed in a stainless steel reactor and then placed in a homogeneous reaction for heating, and then the obtained reactant is filtered, and washed with deionized water and anhydrous ethanol respectively during the filtering process, and the filtered product is placed in a forced air drying oven to dry, and finally a black carbon-coated Sn4P3@C material is obtained; Step (6) Sn4P3 / CoS2@rGO@C material SnCl4 alcohol solution is dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred, and the solution is centrifuged and washed to obtain a CoSn(OH)6@GO composite material. CoSn(OH)6@GO is dissolved in a sodium hydroxide solution by stirring, TAA and the carbon-coated Sn4P3@C prepared in step (5) are weighed and added to the above solution, and then deionized water is added and stirred continuously. The solution is then heated and kept warm in an oven. After natural cooling, the solution is centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material.

[0010] The first technical purpose of the present invention is achieved through the following technical solutions: Preferably, step (1) SnS2 material Add 10-20 ml of concentrated hydrochloric acid to 0.01-0.58 g of tin tetrachloride aqueous solution, and then mix with 2.9-5 g of sodium sulfide (Na2S). Transfer the first mixed solution to a reactor for hydrothermal reaction for 10-15 minutes. After the reaction, a wet precipitate is obtained. The obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material.

[0011] The invention has the advantages that SnS2 is an n-type wide bandgap semiconductor, and a SnS2 powder is synthesized by a hydrothermal method, which has the characteristics of high theoretical reversible capacity, low cost, high content, easy synthesis, high safety, etc.

[0012] Preferably, in step (2), SnS2@GC material Weigh 0.01-0.2 g of glucose and add it to 50-100 ml of polytetrafluoroethylene lining, then add 0.01-0.34 g of SnS2 material prepared in step (1), then add 20-80 ml of deionized water and ultrasonically stir for 1-20 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 100-150 ° C, the reaction time to 1-10 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 10-50 ° C to obtain glucose hydrolysis material SnS2@GC.

[0013] The advantage of the present invention is that carbon coating is carried out by a hydrothermal method, and finally the surface carbon layer is carbonized at high temperature, which improves the conductivity of the material, prevents direct contact between SnS2 and the electrolyte, and avoids the material from pulverizing and falling off the electrode due to repeated expansion and contraction of the material volume, causing capacity decay.

[0014] The second technical purpose of the present invention is achieved through the following technical solutions: Preferably, in step (3), SnS2@C material 0.01-0.2 g of SnS2@GC prepared in step (2) is placed in a porcelain boat, which is then placed in the center of a hard glass tube and placed on a tubular furnace. Argon gas is introduced, and the tubular furnace is set to heat up to 300-600°C at a rate of 1-5°C / min. The temperature is then maintained at this temperature for 1-6 h, and naturally cooled to room temperature to obtain a black material, namely SnS2@C.

[0015] The present invention has the advantage that a carbon-coated material is prepared by a two-step hydrothermal method, the synthesized material has a complete and uniform spherical morphology, the material particle size distribution is from several hundred nanometers to several microns, it has good cycle performance and rate capability, and the electrochemical performance is significantly improved.

[0016] Preferably, in step (4), Sn@C 0.01-0.2 g of SnS2@C prepared in step (3) is placed in a porcelain boat, which is then placed in the center of a hard glass tube and placed on a tubular furnace. An argon mixed gas (H2 / Ar) is introduced, and a heating program of the tubular furnace is set to heat the temperature to 300-600°C at a rate of 1-5°C / min, then kept at this temperature for 1-6 h, and naturally cooled to room temperature to obtain a Sn@C material.

[0017] The advantage of the present invention is that, by means of compounding with carbon materials, the problem of volume expansion is suppressed and alleviated to a certain extent, so that the electrolyte can be easily penetrated, thereby increasing the number of electrochemical reaction sites.

[0018] The third technical objective of the present invention is achieved through the following technical solutions: Preferably, in step (5), the carbon-coated Sn4P3@C material 0.01-0.25 g of the Sn@C material prepared in step (4) and 0.01-0.1 g of red phosphorus are mixed and ground in a mortar for 5-15 min to fully mix the two materials, and then added to 50-100 ml of a polytetrafluoroethylene liner, to which 10-80 ml of ethylenediamine is slowly added and stirred. The liner is placed in a stainless steel reactor and then placed in a homogeneous reaction vessel and heated at 100-200° C. for 10-20 h. The resulting reactant is then filtered and washed with deionized water and anhydrous ethanol for 0.01-3 times respectively during the filtration process. The filtered product is placed in a forced air drying oven and dried at 10-50° C. to finally obtain a black carbon-coated Sn4P3@C material.

[0019] The invention has the advantage that a tin phosphide is prepared by a solvothermal method, the cycle stability is greatly improved, and at the same time, the first charge and discharge efficiency of the material is correspondingly reduced, and the charge and discharge capacity, cycle stability and rate performance are greatly improved.

[0020] Preferably, step (6) Sn4P3 / CoS2@rGO@C material 0.01~1.17ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, and stirred for 5~20min. The solution was centrifuged and washed to obtain a CoSn(OH)6@GO composite material. 5~50mg of CoSn(OH)6@GO was dissolved in 5~20ml of sodium hydroxide solution by stirring. 50~100mg of TAA and 0.01~0.95g of the carbon-coated Sn4P3@C prepared in step (5) were weighed and added to the above solution. Then 5~40ml of deionized water was added and stirred for 0.5~1h. Then the solution was heated to 50~140℃ in an oven and kept warm for 5~12h. After natural cooling, the solution was centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material.

[0021] The invention has the advantage that the composite material synthesized by the coprecipitation method improves the conductivity of the electrode material and the reversibility of the conversion reaction, accelerates the transfer of electrons and increases the diffusion rate of sodium ions, so that the battery has the ability of rapid charge and discharge under large current.

[0022] In summary, the present invention has the following beneficial effects: 1. The present invention has the advantages that SnS2 is an n-type wide bandgap semiconductor, and a SnS2 powder is synthesized by a hydrothermal method, which has the characteristics of high theoretical reversible capacity, low cost, high content, easy synthesis, and high safety; 2. The present invention has the advantages of using a hydrothermal method for carbon coating, and finally carbonizing the surface carbon layer at high temperature, thereby improving the conductivity of the material, preventing direct contact between SnS2 and the electrolyte, and avoiding the material from pulverizing and falling off the electrode due to repeated expansion and contraction of the material volume, causing capacity attenuation; 3. The present invention has the advantages that a two-step hydrothermal method is used to prepare a carbon-coated material, the synthesized material has a complete and uniform spherical morphology, the material particle size distribution ranges from several hundred nanometers to several micrometers, has good cycle performance and rate capability, and the electrochemical performance has been significantly improved; 4. The present invention has the advantage that, by combining with carbon materials, the problem of volume expansion can be suppressed and alleviated to a certain extent, so that the electrolyte can be easily penetrated, and the number of electrochemical reaction sites is increased; 5. The present invention has the advantage that a tin phosphide is prepared by a solvothermal method, and the cycle stability is greatly improved. At the same time, the first charge and discharge efficiency of the material is correspondingly reduced, and the charge and discharge capacity, cycle stability and rate performance are greatly improved; 6. The advantage of the present invention is that the composite material synthesized by the coprecipitation method improves the conductivity of the electrode material and the reversibility of the conversion reaction, accelerates the transfer of electrons and increases the diffusion rate of sodium ions, so that the battery has the ability to quickly charge and discharge under large currents. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The invention relates to a method for preparing a negative electrode material for a sodium ion battery. DETAILED DESCRIPTION

[0024] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Without departing from the spirit and substance of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention are within the scope of the present invention.

[0025] If not specifically stated, the technical means used in the examples are conventional means known to those skilled in the art. In addition, all the raw materials used in the examples are known commercial products. Example 1

[0026] Step (1) SnS2 material 10 ml of concentrated hydrochloric acid is added to 0.3 g of tin tetrachloride aqueous solution, and then mixed with 4.2 g of sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction for 10 minutes, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material; Step (2) SnS2@GC material Weigh 0.04 g of glucose and add it to 55 ml of polytetrafluoroethylene liner, then add 0.04 g of SnS2 material prepared in step (1) thereto, then add 30 ml of deionized water and ultrasonically stir for 6 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 115 ° C, the reaction time to 4 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 20 ° C to obtain glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material 0.03 g of SnS2@GC prepared in step (2) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace. Argon gas was introduced, and the tube furnace was set to heat up to 360°C at a rate of 2.5°C / min, and then kept at this temperature for 3 h, and naturally cooled to room temperature to obtain a black material, namely SnS2@C; Step (4) Sn@C 0.03 g of SnS2@C prepared in step (3) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace, and argon mixed gas (H2 / Ar) was introduced. The tube furnace was set to heat up to 360°C at a rate of 2.5°C / min, and then kept at this temperature for 3 hours, and naturally cooled to room temperature to obtain Sn@C material; Step (5) Carbon coating of Sn4P3@C material 0.03 g of the Sn@C material prepared in step (4) and 0.03 g of red phosphorus were mixed and ground in a mortar for 7 min to fully mix the two materials, added to 65 ml of polytetrafluoroethylene liner, 25 ml of ethylenediamine was slowly added thereto and stirred, the liner was placed in a stainless steel reactor and placed in a homogeneous reaction and heated at 115°C for 12 h, and then the obtained reactant was filtered and washed with deionized water and anhydrous ethanol for 0.3 times respectively during the filtering process, and the filtered product was placed in a forced air drying oven at 13°C to finally obtain a black carbon-coated Sn4P3@C material; Step (6) Sn4P3 / CoS2@rGO@C material 0.09 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred for 12 min, and the solution was centrifuged to obtain a CoSn(OH)6@GO composite material. 12 mg of CoSn(OH)6@GO was dissolved in 12 ml of sodium hydroxide solution by stirring. 60 mg of TAA and 0.02 g of the carbon-coated Sn4P3@C prepared in step (5) were weighed and added to the above solution. Then 15 ml of deionized water was added and stirred for 0.7 h. Then the solution was heated to 65°C in an oven and kept warm for 7 h. After natural cooling, the solution was centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material. Example 2

[0027] Step (1) SnS2 material 10 ml of concentrated hydrochloric acid is added to 0.3 g of tin tetrachloride aqueous solution, and then mixed with 4.2 g of sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction for 12 minutes, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material; Step (2) SnS2@GC material Weigh 0.05 g of glucose and add it to 60 ml of polytetrafluoroethylene liner, then add 0.05 g of SnS2 material prepared in step (1) thereto, then add 35 ml of deionized water and ultrasonically stir for 7 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 120 ° C, the reaction time to 5 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 25 ° C to obtain glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material 0.04 g of SnS2@GC prepared in step (2) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace. Argon was introduced, and the temperature of the tube furnace was set to 370°C at a rate of 3°C / min. The temperature was then kept at this temperature for 4 h and naturally cooled to room temperature to obtain a black material, namely SnS2@C. Step (4) Sn@C 0.04 g of SnS2@C prepared in step (3) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace, and argon mixed gas (H2 / Ar) was introduced. The tube furnace was set to heat up to 370°C at a rate of 3°C / min, and then kept at this temperature for 4 hours, and naturally cooled to room temperature to obtain Sn@C material; Step (5) Carbon coating of Sn4P3@C material 0.04 g of the Sn@C material prepared in step (4) and 0.04 g of red phosphorus were mixed and ground in a mortar for 8 min to fully mix the two materials, added to 70 ml of polytetrafluoroethylene liner, 30 ml of ethylenediamine was slowly added thereto and stirred, the liner was placed in a stainless steel reactor and placed in a homogeneous reaction and heated at 120°C for 13 h, and then the obtained reactant was filtered and washed with deionized water and anhydrous ethanol 0.4 times respectively during the filtering process, and the filtered product was placed in a forced air drying oven at 15°C to finally obtain a black carbon-coated Sn4P3@C material; Step (6) Sn4P3 / CoS2@rGO@C material 0.12 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred for 15 min, and the solution was centrifuged to obtain a CoSn(OH)6@GO composite material. 20 mg of CoSn(OH)6@GO was dissolved in 12 ml of sodium hydroxide solution by stirring, 70 mg of TAA and 0.03 g of the carbon-coated Sn4P3@C prepared in step (5) were weighed and added to the above solution, followed by addition of 20 ml of deionized water, and continued stirring for 0.8 h. The solution was then heated to 70°C in an oven and kept warm for 8 h. After natural cooling, the solution was centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material. Example 3

[0028] Step (1) SnS2 material 10 ml of concentrated hydrochloric acid is added to 0.3 g of tin tetrachloride aqueous solution, and then mixed with 4.2 g of sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction for 13 minutes, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material; Step (2) SnS2@GC material Weigh 0.08 g of glucose and add it to 70 ml of polytetrafluoroethylene liner, then add 0.08 g of SnS2 material prepared in step (1) thereto, then add 40 ml of deionized water and ultrasonically stir for 8 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 130 ° C, the reaction time to 8 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 40 ° C to obtain glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material 0.06 g of SnS2@C prepared in step (3) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace. Argon was introduced, and the temperature program of the tube furnace was set to increase the temperature to 400°C at a rate of 4°C / min, and then kept at this temperature for 5 hours, and naturally cooled to room temperature to obtain a black material, namely SnS2@C; Step (4) Sn@C 0.06 g of SnS2@C prepared in step (3) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace, and argon mixed gas (H2 / Ar) was introduced. The tube furnace was set to heat up to 400°C at a rate of 4°C / min, and then kept at this temperature for 5 hours, and naturally cooled to room temperature to obtain Sn@C material; Step (5) Carbon coating of Sn4P3@C material 0.20 g of the Sn@C material prepared in step (4) and 0.09 g of red phosphorus were mixed and ground in a mortar for 10 min to fully mix the two materials, added to 80 ml of polytetrafluoroethylene liner, 50 ml of ethylenediamine was slowly added thereto and stirred, the liner was placed in a stainless steel reactor and placed in a homogeneous reaction and heated at 150°C for 15 h, and then the obtained reactant was filtered and washed twice with deionized water and anhydrous ethanol during the filtering process, and the filtered product was placed in a forced air drying oven at 20°C to finally obtain a black carbon-coated Sn4P3@C material; Step (6) Sn4P3 / CoS2@rGO@C material 0.13 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred for 18 min, and the solution was centrifuged to obtain a CoSn(OH)6@GO composite material. 30 mg of CoSn(OH)6@GO was dissolved in 15 ml of sodium hydroxide solution by stirring. 80 mg of TAA and 0.80 g of the carbon-coated Sn4P3@C prepared in step (5) were weighed and added to the above solution. Then 30 ml of deionized water was added and stirred for 0.9 h. Then the solution was heated to 100 °C in an oven and kept warm for 10 h. After natural cooling, the solution was centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material. Example 4

[0029] Step (1) SnS2 material 10 ml of concentrated hydrochloric acid is added to 0.3 g of tin tetrachloride aqueous solution, and then mixed with 4.2 g of sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction for 14 minutes, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material; Step (2) SnS2@GC material Weigh 0.2 g of glucose and add it to 100 ml of polytetrafluoroethylene liner, then add 0.34 g of SnS2 material prepared in step (1) thereto, then add 80 ml of deionized water and ultrasonically stir for 20 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 150 ° C, the reaction time to 10 h, after the reaction is completed, naturally cool to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 50 ° C to obtain glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material 0.2 g of SnS2@GC prepared in step (2) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace. Argon was introduced, and the temperature of the tube furnace was set to 600°C at a rate of 5°C / min, and then kept at this temperature for 6 hours, and naturally cooled to room temperature to obtain a black material, namely SnS2@C; Step (4) Sn@C 0.2 g of SnS2@C prepared in step (3) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace, and argon mixed gas (H2 / Ar) was introduced. The tube furnace was set to heat up to 300-600°C at a rate of 5°C / min, and then kept at this temperature for 6 hours, and naturally cooled to room temperature to obtain Sn@C material; Step (5) Carbon coating of Sn4P3@C material 0.25 g of the Sn@C material prepared in step (4) and 0.1 g of red phosphorus were mixed and ground in a mortar for 15 min to fully mix the two materials, and then added to 100 ml of polytetrafluoroethylene liner, 80 ml of ethylenediamine was slowly added thereto and stirred, and the liner was placed in a stainless steel reactor and placed in a homogeneous reaction and heated at 200°C for 20 h, and then the obtained reactant was filtered and washed with deionized water and anhydrous ethanol for 3 times during the filtering process, and the filtered product was placed in a forced air drying oven at 50°C to finally obtain a black carbon-coated Sn4P3@C material; Step (6) Sn4P3 / CoS2@rGO@C material 1.17 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred for 20 min, and the solution was centrifuged to obtain a CoSn(OH)6@GO composite material. 50 mg of CoSn(OH)6@GO was dissolved in 20 ml of sodium hydroxide solution by stirring. 100 mg of TAA and 0.9 g of the carbon-coated Sn4P3@C prepared in step (5) were weighed and added to the above solution. Then 40 ml of deionized water was added and stirred for 1 h. Then the solution was heated to 140°C in an oven and kept warm for 12 h. After natural cooling, the solution was centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material.

[0030] Comparative Example 1 Step (1) SnS2 material 10 ml of concentrated hydrochloric acid is added to 0.3 g of tin tetrachloride aqueous solution, and then mixed with 4.2 g of sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction for 13 minutes, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material; Step (2) SnS2@GC material Weigh 0.01 g of glucose and add it to 50 ml of polytetrafluoroethylene liner, then add 0.01 g of SnS2 material prepared in step (1) thereto, then add 20 ml of deionized water and ultrasonically stir for 1 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 100 ° C, the reaction time to 1 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 10 ° C to obtain glucose hydrolysis material SnS2@GC; Step (3) Sn@C 0.01 g of SnS2@GC prepared in step (2) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace, and argon mixed gas (H2 / Ar) was introduced. The tube furnace was set to heat up to 300°C at a rate of 1°C / min, and then kept at this temperature for 1 hour, and naturally cooled to room temperature to obtain Sn@C material; Step (4) Carbon coating of Sn4P3@C material 0.01 g of the Sn@C material prepared in step (3) and 0.01 g of red phosphorus were mixed and ground in a mortar for 5 min to fully mix the two materials, added to 50 ml of polytetrafluoroethylene liner, 10 ml of ethylenediamine was slowly added thereto and stirred, the liner was placed in a stainless steel reactor and placed in a homogeneous reaction and heated at 100°C for 10 h, and then the obtained reactant was filtered and washed with deionized water and anhydrous ethanol for 3 times during the filtering process, and the filtered product was placed in a forced air drying oven at 10°C to finally obtain a black carbon-coated Sn4P3@C material; Step (5) Sn4P3 / CoS2@rGO@C material 0.01 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred for 5 min, and the solution was centrifuged to obtain a CoSn(OH)6@GO composite material. 5 mg of CoSn(OH)6@GO was dissolved in 5 ml of sodium hydroxide solution by stirring. 50 mg of TAA and 0.01 g of the carbon-coated Sn4P3@C prepared in step (4) were weighed and added to the above solution. Then 5 ml of deionized water was added and stirred for 0.5 h. Then the solution was heated to 50°C in an oven and kept warm for 5 h. After natural cooling, the solution was centrifuged to obtain a CoS2@rGO@C composite material.

[0031] Comparative Example 2 Step (1) SnS2 material 10 ml of concentrated hydrochloric acid is added to 0.3 g of tin tetrachloride aqueous solution, and then mixed with 4.2 g of sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction for 12 minutes, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material; Step (2) SnS2@GC material Weigh 0.03 g of glucose and add it to 50 ml of polytetrafluoroethylene liner, then add 0.03 g of SnS2 material prepared in step (1) thereto, then add 25 ml of deionized water and ultrasonically stir for 5 min to evenly disperse SnS2 in the solution, seal it and put it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 110 ° C, the reaction time to 3 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 15 ° C to obtain glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material 0.02 g of SnS2@GC prepared in step (2) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace. Argon was introduced, and the temperature of the tube furnace was set to 350°C at a rate of 2°C / min. Then, the temperature was kept at this temperature for 2 h, and naturally cooled to room temperature to obtain a black material, namely SnS2@C. Step (4) Sn@C 0.02 g of SnS2@C prepared in step (3) was placed in a porcelain boat, and then the porcelain boat was placed in the center of a hard glass tube and placed on a tube furnace, and argon mixed gas (H2 / Ar) was introduced. The tube furnace was set to heat up to 350°C at a rate of 2°C / min, and naturally cooled to room temperature to obtain Sn@C material; Step (5) CoS2@rGO@C material 0.08 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, and the mixture was stirred for 10 min. The solution was centrifuged and washed to obtain a CoSn(OH)6@GO composite material. 10 mg of CoSn(OH)6@GO was dissolved in 10 ml of sodium hydroxide solution by stirring. 55 mg of TAA and 0.02 g of Sn@C prepared in step (4) were weighed and added to the above solution. Then 10 ml of deionized water was added and the mixture was stirred for 0.6 h. The solution was then heated to 60°C in an oven and kept warm for 6 h. After natural cooling, the solution was centrifuged to obtain a CoS2@rGO@C composite material.

[0032] Comparison of detection experiments: The materials obtained in Examples 1 to 4 and Comparative Example Products 1 and 2 were tested, and the specific testing methods are as follows: Electrochemical Impedance Spectroscopy Test Electrochemical Impedance Spectroscopy (EIS): Measures the ratio of AC potential to current signal as it changes with the sine wave frequency ω, or the impedance phase angle Φ as it changes with ω. By fitting the equivalent circuit of the electrode reaction, the specific parameter values ​​of the components in the equivalent circuit can be obtained. The tested voltage amplitude is 5mV.

[0033] Cyclic voltammetry test Cyclic Voltammetry (CV) is a very commonly used electrochemical measurement method. By applying a voltage that changes at a certain rate and repeatedly scanning in a certain voltage range, the current change curve with respect to voltage is obtained. The scanning voltage range is 0.01V-2V or 0.01 V-2.5V, and the scanning rate is 0.1mV / s.

[0034] Constant current charge and discharge test Constant current charge and discharge test is a test method used to detect the cycle performance of electrode materials when used in batteries. The corresponding electrochemical performance data is obtained by setting the charge and discharge current density and the charge and discharge voltage range. The voltage range for charging and discharging the electrode material is 0.01 V-2V or 0.01V-2.5V, and the current density is 0.1A / g-5A / g.

[0035] Table 1 Electrochemical impedance spectroscopy test results

[0036] As can be seen from Table 1, Example 4 is the best, while Comparative Example 1 is relatively poor. The material maintains electrochemical activity, has good electrochemical cycle performance, has significantly improved cycle stability, retains a relatively low charge and discharge voltage platform, and the cycle efficiency continues to decrease.

[0037] Table 2 Cyclic voltammetry test results

[0038] As shown in Table 2, Example 4 is the best, while Comparative Example 1 is the worst. Carbon coating reduces the amount of SEI film formed on the surface of the material. At the same time, the larger pore size and higher porosity are more conducive to the mass transfer process of the electrolyte to the surface of the material. On the other hand, the matrix Sn4P3 phase contains a mixture of single Sn and SnP 0.94 , their presence improves the conductivity of the material and Na + Ion diffusion efficiency.

[0039] Table 3 Constant current charge and discharge test results

[0040] As shown in Table 3, Example 4 is the best, while Comparative Example 1 is the worst. + The transfer of Na2O3 is hindered, which increases the polarization of the electrochemical reaction. The voltage hysteresis of the three groups of carbon-coated materials is alleviated to varying degrees. This is mainly because the SEI film formed on the surface of the carbon layer has better stability than that formed on the surface of Sn4P3, and the presence of the carbon layer is also beneficial to the Na2O3 + Transfer into the material.

[0041] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to the present embodiment as needed, but they are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: Preparation of SnS2 materials, preparation of SnS2@GC materials, preparation of SnS2@C materials, preparation of Sn@C, preparation of carbon-coated Sn4P3@C materials, and preparation of Sn4P3 / CoS2@rGO@C materials.

2. The method for preparing a negative electrode material for a sodium ion battery according to claim 1, characterized in that: Step (1) SnS2 material Concentrated hydrochloric acid is added to a tin tetrachloride aqueous solution, and then mixed with sodium sulfide (Na2S) to obtain a first mixed solution, and the first mixed solution is transferred to a reactor for hydrothermal reaction, and a wet precipitate is obtained after the reaction is completed; the obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain a SnS2 material; Step (2) SnS2@GC material First, glucose is weighed and added to a polytetrafluoroethylene liner, and then the SnS2 material prepared in step (1) is added thereto, and then deionized water is added and ultrasonically stirred to uniformly disperse the SnS2 in the solution, and then the mixture is sealed and loaded into a stainless steel reactor, and then placed in a homogeneous reactor, and the reaction temperature and reaction time are set. After the reaction is completed, the mixture is naturally cooled to room temperature, and the obtained material is washed with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then placed in a blast drying oven to dry, thereby obtaining a glucose hydrolysis material SnS2@GC; Step (3) SnS2@C material The SnS2@GC prepared in step (2) is placed in a porcelain boat, and then the porcelain boat is placed in the center of a hard glass tube and placed on a tube furnace, argon gas is introduced, and a heating program of the tube furnace is set, the temperature is increased at a rate, and then the temperature is maintained at this temperature, and naturally cooled to room temperature to obtain a black material, namely SnS2@C; Step (4) Sn@C The SnS2@C material prepared in step (3) is placed in a porcelain boat, which is placed in the center of a hard glass tube and moved to a tube furnace, into which a hydrogen-argon mixture (H2 / Ar) is introduced, and the temperature is increased at a program rate, and then the temperature is maintained at this temperature, and naturally cooled to room temperature to obtain a Sn@C material; Step (5) Carbon coating of Sn4P3@C material The Sn@C material prepared in step (4) and red phosphorus are mixed and ground in a mortar to make the two materials fully mixed, and then added to a polytetrafluoroethylene liner, and ethylenediamine is slowly added thereto and stirred, and the liner is placed in a stainless steel reactor and then placed in a homogeneous reaction for heating, and then the obtained reactant is filtered, and washed with deionized water and anhydrous ethanol respectively during the filtering process, and the filtered product is placed in a forced air drying oven to dry, and finally a black carbon-coated Sn4P3@C material is obtained; Step (6) Sn4P3 / CoS2@rGO@C material SnCl4 alcohol solution is dissolved in a graphene oxide solution containing cobalt ions and citrate, stirred, and the solution is centrifuged and washed to obtain a CoSn(OH)6@GO composite material. CoSn(OH)6@GO is dissolved in a sodium hydroxide solution by stirring, TAA and the carbon-coated Sn4P3@C prepared in step (5) are weighed and added to the above solution, and then deionized water is added and stirred continuously. The solution is then heated and kept warm in an oven. After natural cooling, the solution is centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material.

3. The method for preparing a negative electrode material for a sodium ion battery according to claim 2, characterized in that: Step (1) SnS2 material 10-20 ml of concentrated hydrochloric acid is added to 0.01-0.58 g of tin tetrachloride aqueous solution, and then mixed with 2.9-5 g of sodium sulfide (Na2S) to obtain a first mixed solution. The first mixed solution is transferred to a reactor for hydrothermal reaction for 10-15 minutes, and a wet precipitate is obtained after the reaction. The obtained wet precipitate is washed with deionized water and ethanol and then centrifuged to obtain SnS2 material.

4. The method for preparing a negative electrode material for a sodium ion battery according to claim 3, characterized in that: Step (2) SnS2@GC material Weigh 0.01-0.2 g of glucose and add it to 50-100 ml of polytetrafluoroethylene lining, then add 0.01-0.34 g of SnS2 material prepared in step (1), then add 20-80 ml of deionized water and ultrasonically stir for 1-20 min to evenly disperse SnS2 in the solution, seal it and load it into a stainless steel reactor, place it in a homogeneous reactor, set the reaction temperature to 100-150 ° C, the reaction time to 1-10 h, after the reaction is completed, cool it naturally to room temperature, wash the obtained material with deionized water and anhydrous ethanol respectively until the filtrate is clear, and then place it in a forced air drying oven at 0-50 ° C to obtain glucose hydrolysis material SnS2@GC.

5. The method for preparing a negative electrode material for a sodium ion battery according to claim 4, characterized in that: Step (3) SnS2@C material 0.01-0.2 g of SnS2@GC prepared in step (2) is placed in a porcelain boat, which is then placed in the center of a hard glass tube and placed on a tubular furnace. Argon gas is introduced, and the tubular furnace is set to heat up to 300-600°C at a rate of 1-5°C / min. The temperature is then maintained at this temperature for 1-6 h, and naturally cooled to room temperature to obtain a black material, namely SnS2@C.

6. The method for preparing a negative electrode material for a sodium ion battery according to claim 5, characterized in that: Step (4) Sn@C 0.01-0.2 g of SnS2@C prepared in step (3) is placed in a porcelain boat, which is then placed in the center of a hard glass tube and placed on a tubular furnace. An argon mixed gas (H2 / Ar) is introduced, and a heating program of the tubular furnace is set to heat the temperature to 300-600°C at a rate of 1-5°C / min, then kept at this temperature for 1-6 h, and naturally cooled to room temperature to obtain a Sn@C material.

7. The method for preparing a negative electrode material for a sodium ion battery according to claim 6, characterized in that: Step (5) Carbon coating of Sn4P3@C material 0.01-0.25 g of the Sn@C material prepared in step (4) and 0.01-0.1 g of red phosphorus are mixed and ground in a mortar for 5-15 min to fully mix the two materials, and then added to 50-100 ml of a polytetrafluoroethylene liner, to which 10-80 ml of ethylenediamine is slowly added and stirred. The liner is placed in a stainless steel reactor and then placed in a homogeneous reaction vessel and heated at 100-200° C. for 10-20 h. The resulting reactant is then filtered and washed with deionized water and anhydrous ethanol for 0.01-3 times respectively during the filtration process. The filtered product is placed in a forced air drying oven and dried at 10-50° C. to finally obtain a black carbon-coated Sn4P3@C material.

8. The method for preparing a negative electrode material for a sodium ion battery according to claim 7, characterized in that: Step (6) Sn4P3 / CoS2@rGO@C material 0.01-1.17 ml of SnCl4 alcohol solution was dissolved in a graphene oxide solution containing cobalt ions and citrate, and stirred for 5-20 min. The solution was centrifuged and washed to obtain a CoSn(OH)6@GO composite material. 5-50 mg of CoSn(OH)6@GO was dissolved in 5-20 ml of sodium hydroxide solution by stirring. 50-100 mg of TAA and 0.001-0.95 g of the carbon-coated Sn4P3@C prepared in step (5) were weighed and added to the above solution. Then 5-40 ml of deionized water was added and stirred for 0.5-1 h. Then the solution was heated to 50-140°C in an oven and kept warm for 5-12 h. After natural cooling, the solution was centrifuged to obtain a Sn4P3 / CoS2@rGO@C composite material.

Citation Information

Patent Citations

  • Tin-phosphide composite material and preparation method and application thereof

    CN110034283A

  • Anode Active Materials comprising Sn-P Systems For Na Ion Batteries And Manufacturing Methods Thereof

    KR1020160056387A